SISTEM INFORMASI E-RECRUITMENT DOSEN PADA PERGURUAN TINGGI SWASTA - Terttiaavini Terttiaavini; Suzan Agustri (Jurnal Informatika Global)
Expert systems are systems that use information technology to generate analytic thinking approach an expert. Expert systems now widely collaborate with a wide range of disciplines can help in the decision or result in the rapid and precise output. Removed from the problems that often occur in prospective students, the difficulty in determining the course to be taken, efforts should be made to prospective students guidance in order to determine the appropriate course based on their own potential. Psychometric analysis can analyze indicators of IQ and aptitude. This is the proper technique to learn and explore the potential of students. In addition the use of an expert system that is supported by information technology to facilitate the students to know the results of the analysis of IQ, and talent with ease. The initial process of psychometric analyzes performed on the different stages of construction scale item. By way of computing the correlation coefficients and item total correlation results with significance testing using t-test, is expected to produce a valid and reliable item. Further building expertise, necessary to analyze the expert system that includes activities pendefenisian knowledge base and the inference engine. Alternative solutions will be represented in the decision tree model (decision tree).